Investigating the Role of Social Status in Teacher Collaborative Groups. (September 2019) - Sutton, Paul S.; Shouse, Andrew W.
In collaborative groups, teachers negotiate the tension between working as a cohesive group and confronting differences of opinion and practice. Varied status between teachers can complicate their ability to accomplish the goals of collaboration. In this case study, we describe how a group of secondary English teachers redesigned curriculum and explain how status shaped their collaborative practice. We use positioning theory to examine how teachers managed variable status to maintain a collaborative group process. Findings suggest the high-status teacher shaped inclusive collaborative routines that afforded novice teachers the space to initiate discussions focused on problems of practice.